Salivary Duct Cancer Metastasis Mimicking Primary Breast Cancer: A Case Report and Review - Alzuhair, Aisha M.; Gong, Gyungyub; Shin, Hee Jung; Lee, Jong Won; Lee, Sae Byul; Kim, Jisun; Ko, Beom Seok; Son, Byung Ho; Ahn, Sei Hyun; Chung, Il Yong (Journal of breast cancer, 2019)
Secondary breast malignancy is a rare occurrence, accounting for less than 2% of all breast malignancies. Salivary duct carcinoma (SDC) metastasizing to the breast has not been reported previously. This report presents the case of a woman who was initially diagnosed with and treated for parotid carcinoma. Two years later, during a follow-up visit, a breast lump was discovered, which was diagnosed as primary breast cancer and managed surgically. After surgery, hematoxylin and eosin and immunohistochemical staining revealed that the breast tumor had the same features as her primary SDC. Here, we present a confusing case of SDC metastasis to the breast that mimicked triple-negative breast cancer.